2012
DOI: 10.1021/ol302570k
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Alotaketal A

Abstract: The total synthesis of the cAMP signaling pathway activator (-)-alotaketal A is reported. A convergent approach to the unusual alotane sesterterpenoid skeleton was employed, exploiting a remarkable LiDBB-mediated coupling of an (R)-carvone-derived δ-lactone with an allyl bromide side chain, followed by spiroacetalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…A recent study has shown that simple semisynthetic modification of natural ingenol esters enhanced their LRA potency and reduced their toxicity, demonstrating that SAR-driven improvement in therapeutic index is possible in these terpenoid families . Two total syntheses of alotaketal A have been reported, which provide access to this scaffold and analogues for SAR. , Therefore, the Phorbas sesterterpenoids 2 , 3 , 8 , and 14 reported herein represent a new set of terpenoid scaffolds that are interesting lead structures for SAR-driven development of LRA cell biology tools and drug candidates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that simple semisynthetic modification of natural ingenol esters enhanced their LRA potency and reduced their toxicity, demonstrating that SAR-driven improvement in therapeutic index is possible in these terpenoid families . Two total syntheses of alotaketal A have been reported, which provide access to this scaffold and analogues for SAR. , Therefore, the Phorbas sesterterpenoids 2 , 3 , 8 , and 14 reported herein represent a new set of terpenoid scaffolds that are interesting lead structures for SAR-driven development of LRA cell biology tools and drug candidates.…”
Section: Discussionmentioning
confidence: 99%
“…716 by two independent groups have conrmed the absolute conguration. 717,718 Four sesterterpenoids, phorone A 855, isophorbasone A 856, ansellone B 857 and phorbasone A acetate 858, were isolated from a S. Korean Phorbas sp. Compounds 857 and 858, described in the paper's supporting information, were low mM inhibitors of NO production in LPS-stimulated RAW 264.7 cells, while 855 and 856 are the rst examples of two new carbon skeletons.…”
Section: Spongesmentioning
confidence: 99%
“…The potent and wide array of biological activities of alotaketals and phorbaketals have attracted considerable synthetic interest. The groups of Yang, and Dalby accomplished the elegant total synthesis of 1 by similar strategies, which involved late‐stage construction of the C ring through a Barbier‐type reaction and spiroketalization. Recently, the groups of Brimble and Bray disclosed two efficient strategies for the tricyclic spiroketal core, which unfortunately could not be elaborated to the natural products.…”
Section: Figurementioning
confidence: 99%